Effect of group size and regrouping on physiological stress and behavior of dairy calves - Jing LYU; Chao Wang; Xun-wu ZHAO; Er-yu MIAO; Zhi-peng WANG; Yuan XU; Xiu-juan BAI; Jun BAO (Journal of Integrative Agriculture, 2023)
Mixing or regrouping of calves from different pens is a common animal management practice on the farm, which frequently occurs after weaning and has a negative effect on calve welfare. Social integration before regrouping may relieve stresses, but more evidences are needed to verify this hypothesis. The present study aimed to investigate acute physiological and behavioral variations of individually- or group-housed calves after being introduced into a mixed group. A total of 132 postnatal calves were randomly divided into groups of 1, 3, 6 and 12 animals (S, G3, G6, and G12; 6 replicates in each group) until 59 days of age. At 60 days of age, every two replicates from different groups (S, G3, G6 and G12) were introduced in a larger pen which containing 44 of the aboved experimental calves. Before and after regrouping, physiological parameters of stress, including heart rate (HR), saliva cortisol (S-CORT), saliva secretory immunoglobulin A (SIgA), interleukin-2 (IL-2), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α) levels, and behavioral responses were recorded. After regrouping, HR and S-CORT increased immediately (P<0.05), and higher (P<0.05) levels of such molecules were found in S calves compared to those in group-housed calves. Levels of SIgA and IL-2 were decreased (P<0.05), and the lowest (P<0.05) IL-2 values were found in S calves compared to those in group-housed calves. In addition, the introduced calves displayed a distinct behavior, including altered active and rest time, which was associated with negative emotions triggered by the novel surroundings. Allogrooming, play, exploration behaviors and lying time were increased significantly (P<0.05) in group-housed calves than those in S calves. Conversely, self-grooming, aggressive behaviors, standing and walking time were increased (P<0.05) in S calves than those in group-housed calves. These findings suggest that individually-housed calves may be more susceptible to stressors arising from regrouping than group-housed calves, which consequently negatively affected behavioral and neuroendocrine responses. Furthermore, moving calves with previous social experience may help mitigate regrouping stress.